Analysis of the shot displacements performed by professional tennis players: a case study - Kim, H.; Jung, K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Performance analysis in tennis was conducted with the aims of tactical evaluation, movement analysis, and database development [1, 2]. Players strategically execute shots to control court space and to disrupt stable relations during a competition. Players attempt to make their opponent cover more ground forcefully [3]. This study focused on shot displacements dispersed across the court, examining whether the area of shot displacements can serve as indicators of tactics and overall performance. We hypothesized that winners occupy a great shot displacement area, reflecting superior tactical performance since highly skilled players make opponents move back and forth or left and right. METHODS: A first-round professional tennis match from the Australian Open was selected to leverage expected level differences between seed and non-seed players. Kinovea software converted high-definition video (720p) to image sequences. Images containing ball bouncing on the court were imported to a custom-written MATLAB enabling shot displacements tracking. The entire court was divided into 16 sections and the area of shot displacements for each section was calculated using a convex hull algorithm. RESULTS: In the first-round match, the seed player exhibited a total shot displacements area of 35.34 m2, which is greater than non-seed player`s 26.87 m2. Particularly in section 1 and 2 at the intersection of endline and sideline, the seed player had 3.58 m2, whereas the non-seed player had 2.09 m2. In section 2, the seed player also showed a greater shot displacements area than non-seed player. Respectively, 3.86 m2 for seed player and 2.99 m2 for non-seed player were shown, indicating seed player made more shots to the far side corners to make opponents move forcefully. CONCLUSION: This study underscores the significance of shot displacement analysis as a valuable indicator of tactics and performance in tennis. Tennis players these days emphasize stroke plays over serve-and-volley strategies. The seed player consistently utilized a greater shot displacements area than the non-seed player in most of sections, affirming its potential as an additional tool for performance evaluation, in conjunction with traditional notational analysis. Future studies should expand the dataset to generalize these findings across more tennis matches.